A CENTURY OF INFLUENZA IN TAIWAN: EPIDEMIOLOGICAL PATTERNS AND THE EVOLUTION OF GENOMIC SURVEILLANCE - Gong, Yu-Nong (UNG, 2026)
Influenza remains a major global public health concern, and Taiwan has experienced repeated pandemic waves, seasonal epidemics, and zoonotic threats over the past century. This review aims to summarize the historical development of influenza in Taiwan and its implications for surveillance and preparedness. A systematic literature review was conducted using scientific publications, government reports, historical archives, and genomic surveillance data accessed through indexed academic platforms. All sources were synthesized to describe pandemic history, seasonal patterns, avian influenza risks, and advancements in laboratory-based monitoring. The findings show that Taiwan was significantly affected by major pandemics, including the 1918 H1N1, 1957 H2N2, 1968 H3N2, and 2009 H1N1 outbreaks, each contributing to improvements in health system readiness. Seasonal influenza in Taiwan displays a dual-peak pattern driven by local transmission and international virus introductions, with shifting dominance among H1N1, H3N2, and influenza B. Zoonotic threats from H5N1 and H7N9 continue to demand strict poultry surveillance and One Health coordination. Since 2000, Taiwan’s nationwide laboratory network has strengthened rapid detection, genome sequencing, mutation analysis, and global migration modeling, supporting more effective responses to emerging strains. In conclusion, Taiwan’s robust surveillance capacity and genomic monitoring have enhanced preparedness for influenza threats. Nevertheless, rapid viral evolution, global mobility, and persistent zoonotic risks highlight the need for continuous genomic surveillance, improved international collaboration, and optimized vaccine strategies.